1992
DOI: 10.1104/pp.100.2.1062
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Proplastids to Amyloplasts in Tobacco Cultured Cells Is Accompanied by Changes in the Transcriptional Activities of Plastid Genes

Abstract: When tobacco (Nicotiana tabacum L.) cultured cells at the stationary phase were transferred to culture medium that contained cytokinin (benzyladenine) instead of auxin (2,4-dichlorophenoxyacetic acid), proplastids in the BY-2 cells were converted to amyloplasts within 48 h. The data obtained from in vitro transcription assays using isolated plastid-nucleoids (nuclei) strongly suggested that amyloplast formation in BY-2 cells was accompanied by changes in the transcriptional activities of plastid genes.Plastid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…It is well documented that cytokinins play a major role in promoting cell division (Letham, 1963;Nishinan and Syono, 1980;Summons et al, 1980), but there is no information on their effect on endosperm cell number in maize. Moreover, it has been shown that cytokinins can promote chloroplast biogenesis and development (Parthier, 1979;Parthier et al, 1982;Caers and Vendrig, 1986) and convert proplastids to amyloplasts in cultured tobacco cells (Sakai et al, 1992). However, their effect on amyloplast biogenesis in cereal grains has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that cytokinins play a major role in promoting cell division (Letham, 1963;Nishinan and Syono, 1980;Summons et al, 1980), but there is no information on their effect on endosperm cell number in maize. Moreover, it has been shown that cytokinins can promote chloroplast biogenesis and development (Parthier, 1979;Parthier et al, 1982;Caers and Vendrig, 1986) and convert proplastids to amyloplasts in cultured tobacco cells (Sakai et al, 1992). However, their effect on amyloplast biogenesis in cereal grains has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be a consequence of the differentiation status of both plastid types. Although etioplasts differentiate into chloroplasts after illumination, BY-2 plastids remain non-photosynthetic in the light and can only differentiate into amyloplast-like organelles after hormone depletion (37). It is also possible that the BY-2 plastid metabolism reflects the long term adaptation of the BY-2 cell culture to the carbohydrate supply from the growth medium.…”
Section: Fig 3 Comparison Of Different Etioplast Isolates By Proteimentioning
confidence: 99%
“…This regulation is postulated to be accomplished by plastid-to-nucleus signaling, 1,2 although the overall signal transduction pathway(s) are not well characterized. By applying a specific differentiation system in tobacco Bright Yellow-2 (BY-2) cultured cells, 3,4 we recently reported that the regulatory system of nuclear gene expressions modulated by a plastid signal was also observed during differentiation of plastids into amyloplasts. 5 While retrograde signaling from plastids was previously speculated to consist of several independent pathways, we found inhibition of OGE and perturbation in the cellular content of one tetrapyrrole intermediate, heme, seemed to interact to regulate amyloplast differentiation.…”
mentioning
confidence: 99%